THE HALF-CENTURY UNIVERSITY - Mahammatov Akram (Web of Journals Publishing, 2024)
This article is devoted to the creation of Jizzakh State Pedagogical University and talks about the general activities of the university for about 50 years. Valuable information is provided about the participation of statesman and public figure Sharof Rashidov in the process of establishing the university.
Keywords: Jizzakh oasis, institute, university, rector, vice-rector, faculty, research work, scientific potential, material and technical base, educational process.